Experimental & Numerical Investigation on the effect of inlet shape of inclined heated channel - Mohd Azrul bin Samsuddin, Mohd Azrul (Universiti Teknologi Petronas, 2010)
A solar chimney, often referred to as a thermal chimney is a way of improving the natural ventilation of buildings by using convection of air heated by passive solar energy. A solar chimney can also be used for electricity generation. A simple description of a solar chimney is that of a vertical shaft utilizing solar energy to enhance the natural stack ventilation through a building. The Solar Chimney has three main components which are the canopy, absorber (collector) and the chimney. The difference in temperature created by the sun on a collector will cause a current of air in a passage strong enough to operate a conventional wind turbine to generate electricity. There are attempted to analysis four inlet configurations in order to define the best inlet which has the highest air flow for power generation.